Prosesi Adat Molo'opu di Gorontalo Utara dalam Perspektif Sosiologi Pendidikan Islam - Muh. Arif; Mahfud Harim (Jurnal Hikmatuna, 2019)
The article aims to explore the Islamic education values in the Molo'opu tradition in Gorontalo Utara. This research used a qualitative technique and an analytic-descriptive approach from a socio-anthropological perspective to understand the Molo'opu tradition. It was found that the Molo'opu tradition is a ceremonial activity that involves escorting an officer from their home to their official residence. The Molo'opu tradition takes place at two locations, namely the private house (To'opu lo Hihilawo) and the official residence (To'opu Yiladia). Islamic education values present in the Molo'opu tradition include human values, ethical values, social values, discussion values, cultural values, and Shariah values. All of these values contribute to Islamic education by rewarding the leader or guest participating in the Molo'opu tradition and by emphasizing moral teachings through the use of tuja'i words.